EFISIENSI EKSEKUSI JAMINAAN FIDUCIA PASCA PUTUSAAN MK NO: 18/PUU-XVIII/2019 TERHADAB PERUSHAAN PEMBIAYAAN (MULTI FINANCE) - Pinto Utomo; Budiarsih Budiarsih; Evi Konggres (Maleo Law Journal, 2020)
Decicion of the Constitotional Courst nomber 18/PUUU-VXIII / 2019 annulls some of the phrases and their explanations contained in article 15 paragraph (2) along with their explanations and faragraph (3) of the fiduusiary Acts contrary to thee 1945 Constitution as long  it is not edited as interpreted by thi Panel off Judges off the Court Thee Constitution contained in the related decision. The implementation of fiduciary guarantee execution is no longer as effective and as efficient as before. This paper focuses on how efficient is the implementation of Fiduciary Guarantee after the Decision of Mk No: 18 / PUU-XVII / 2019 towards Financing Companies. The normative juridical method for reviewing written legislation and legal principles by examining the rules of legal norms. The results of the study found that fiduciary guarantees still have or are attached to an executorial power whose decisions are the same as court decisions that have legal power permanent, and thi creditur as the recipent of fidusiaary retains full authority tu be able to carry out his own execution (parate execution), as long as the debtor has "breach of promise" both recognized by the debtor or based on legal remedies, and there is no objection to voluntarily handing over the objec of fidosiary guarantee, if exsecution of fiduciary guarantees must always be carried out through the mediation process of the court, thereby eliminating the specificity of fiduciary guarantees as referred to in the explanation of Articl 15 paragrap (3) off thi Fiduciary Guarantee Act, namely the ease in carrying out their executions so that the execution of fiduciary guarantees is ineffective and inefficient.Keywords : Guarantee. Fidusia